Discourse Analysis: A Comparative Case Study of Two Literary Works of English and Persian Female Writers from Socio-Cognitive Perspective - Aydin Ghorbanzad (International Journal of Practical and Pedagogical Issues in English Education)
Language as the sole mean of communication has always been a tool for power abuse by authorities and other media owners through various channels and tribunes worldwide to divide people based on ethnicity and nation-state; this has become a widespread phenomenon in the present age and has led to a cultural and moral separation among people across the globe. Accordingly, due to the political incidents over the last decades between Iran and most Western countries, people living in Western countries are misguided by biased language manipulation and interpretations by authorities. As a multi-disciplinary research, the present study attempted to provide a realistic and scientific viewpoint toward language manipulation by adopting Discourse Analysis (DA) methodology. Two well-known literary works written by female authors were chosen to be analyzed, namely, A Room of One's Own and Suvashun. Halliday's (1985) framework was utilized to probe the subject matter and extract explicit and implicit ideational concepts. Results have indicated similarities and differences in the feminine discourses in the research samples. The current study's findings shall benefit intellectual and academic individuals in particular and the whole society at large.